Effect of fermentation of herbal products on growth performance, breast meat quality, and intestinal morphology of broiler chickens: a meta-analysis - Danung Nur Adli; Mohammad Miftakhus Sholikin; Tri Ujilestari; Bilal Ahmed; Ayesha Sadiqqua; Muhammad Ainsyar Harahap; Ahmad Sofyan; Sugiharto Sugiharto (Italian Journal of Animal Science)
Although it has widely been applied in human applications for therapeutic purposes, the use of fermented herbal products to improve growth performance in broiler chickens is still disputable. This study aimed to compare the effectiveness of fermented versus unfermented herbal products in improving the growth performance, breast meat quality, and small intestinal morphology of broiler chickens and to determine the optimal conditions according to meta-analysis and response surface methodology. The database was developed based on 23 articles comprising 123 data points collected in 2023. The metadata was analysed using OpenMEE and R, with the inclusion of fermented herbal products as fixed factors and individual studies as random factors. The optimal dosage was determined using response surface methodology (RSM). A significant difference (p < 0.05) was detected between unfermented and fermented herbal products in terms of broiler body weight gain, feed intake, and feed conversion ratio (FCR) during the starter phase. The principal notable impact is associated with the utilisation of Zingiber officinale and fermenting agents, such as Lactobacillus sp. and Saccharomyces cerevisiae. Both treatments resulted in a substantial reduction (p < 0.01) in the FCR. According to the meta-regression, growth performance exhibited a consistent pattern with the results of the meta-analysis, including overall production parameters during the starter phase (p < 0.05), such as body weight, average daily gain, and daily feed intake. Significant differences were detected in breast meat quality, particularly in terms of polyunsaturated fatty acids (p < 0.05), as well as in the morphology of the digestive tract, such as duodenum crypt depth, villus height, and their ratio (p < 0.05). These findings indicate that fermenting dietary herbs can enhance the growth, breast meat quality, and intestinal morphology of broiler chickens, particularly during their initial growth phase. It is envisaged that broiler producers ferment herbs before adding them to chicken feed at ∼26.3 g/kg.